(untitled) (Research, Society and Development, 2020)
The change of the student profile has fostered the reinvention of education over the past two decades, prioritizing the development of competences, skills and values more consistent with the current job market. In this context, active methodologies prove to be effective in improving the teaching and learning processes, but they are still used timidly in vocational high school, especially in Exact Science courses. Thus, the objectives of this article are to analyze and discuss existing research about the usage of active methods in the brazilian scenario and, specifically, to study the use of these methodologies in an integrated technical course in Buildings. To accomplish these purposes, a bibliometric study about the subject in Brazil was carried out and the research was developed through interviews and questionnaires along with teachers and students of the mentioned course. The results provide an overview of the usage of these methodologies in the brazilian scenario, showing advances in their use and pointing out positive aspects, difficulties and challenges perceived in the implementation of these practices. The experiences lived in the Buildings course confirmed the results found in the bibliometric study and pointed out ways to improve the use of these methodologies in that course.